Effect of the Cascade Injection Molding on the Filling Behaviour - Habrman, Martin; Ráž, Karel; Kalina, Tomáš (Manufacturing Technology Journal, 2019)
This paper deals with different ways of injection molding. A plastic part can be generally filled many ways. Use of more than one gate is common in a plastic industry. Cascade molding can affect the final properties of the product, especially by the number of gates, timing of closing - opening and by the order of individual gates. A simple plastic box is used as a reference part in this paper. It is a longitudinal part with one side longer than the others. There are ribs on the bottom side of the box. The injection system is located on the bottom side of the box. The filling process is considering five individual gates. All possible filling variants are compared with respect to temperature, pressure and number of weld lines. Sequential filling from the central point of the box is the most suitable option.
Keywords: Multi-gate Injection Molding; Hot Runner System